Effect of exercise training on subjective parameters in patients with obstructive sleep apnea: a systematic review and meta-analysis - Lins-Filho, Ozeas L.; Pedrosa, Rodrigo Pinto; Gomes, Jessica M.L. [UNESP]; Dantas Moraes, Sandra L.; Vasconcelos, Belmiro Cavalcanti Egito; Lemos, Cleidiel Aparecido Araujo; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2020)
Obstructive sleep apnea (OSA) has many effects on subjective parameters of the disease, such as reduction in quality of life (QoL), sleep quality (SQ), and increases in daytime sleepiness. Studies have reported the beneficial effect of exercise training on OSA severity; however, whether it improves subjective parameters remains unclear. The purpose of the present review was to investigate the effect of exercise training on QoL, daytime sleepiness, and SQ in adults with OSA by summarizing the results of clinical trials. The study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was registered in PROSPERO. A systematic review of the PubMed, Scopus, and Cochrane (CENTRAL) databases was conducted. Risk of bias analysis was performed using the Cochrane tool, and Review Manager version 5.2 (R Foundation for Statistical Computing, Vienna, Austria) was used to perform the meta-analysis. Of the 1573 studies initially retrieved, 8 relevant studies with 228 participants were included in the analysis. The studies presented moderate risk of bias. Exercise training significantly improved QoL (mean difference, 12.9 [95% confidence interval (CI) 6.4 to 19.5]) and SQ (mean difference, −2.0 [95% CI -3.6 to −0.5]), and reduced daytime sleepiness (mean difference, −3.7 [95% CI -6.1 to −1.2]), and OSA severity (mean difference, −11.4 [95% CI -13.4 to −9.4 events/h]). Thus, physical exercise training was effective in improving subjective parameters and reducing the severity of OSA. Additional randomized clinical trials, however, should be performed to confirm these findings.
Keywords: Exercise; Quality of life; Sleep apnea syndromes